A Comparison of Whole Genome Sequencing to Multigene Panel Testing in Hypertrophic Cardiomyopathy Patients. (October 2017) - Cirino, Allison L.; Lakdawala, Neal K.; McDonough, Barbara; Conner, Lauren; Adler, Dale; Weinfeld, Mark; O'Gara, Patrick; Rehm, Heidi L.; Machini, Kalotina; Lebo, Matthew; Blout, Carrie; Green, Robert C.; et al.
Abstract : Background—: As DNA sequencing costs decline, genetic testing options have expanded. Whole exome sequencing and whole genome sequencing (WGS) are entering clinical use, posing questions about their incremental value compared with disease-specific multigene panels that have been the cornerstone of genetic testing. Methods and Results—: Forty-one patients with hypertrophic cardiomyopathy who had undergone targeted hypertrophic cardiomyopathy genetic testing (either multigene panel or familial variant test) were recruited into the MedSeq Project, a clinical trial of WGS. Results from panel genetic testing and WGS were compared. In 20 of 41 participants, panel genetic testing identified variants classified as pathogenic, likely pathogenic, or uncertain significance. WGS identified 19 of these 20 variants, but the variant detection algorithm missed a pathogenic 18 bp duplication in myosin binding protein C ( MYBPC3 ) because of low coverage. In 3 individuals, WGS identified variants in genes implicated in cardiomyopathy but not included in prior panel testing: a pathogenic protein tyrosine phosphatase, non-receptor type 11 ( PTPN11 ) variant and variants of uncertain significance in integrin-linked kinase ( ILK ) and filamin-C ( FLNC ). WGS also identified 84 secondary findings (mean=2 per person, range=0–6), which mostly defined carrier status for recessive conditions. Conclusions—: WGS detected nearly all variants identified on panel testing, provided 1 new diagnostic finding, and allowed interrogation of posited disease genes. Several variants of uncertain clinical use and numerous secondary genetic findings were also identified. Whereas panel testing and WGS provided similar diagnostic yield, WGS offers the advantage of reanalysis over time to incorporate advances in knowledge, but requires expertise in genomic interpretation to appropriately incorporate WGS into clinical care. Clinical Trial Registration—: URL:https://clinicaltrials.gov . Unique identifier: NCT01736566. Abstract : Supplemental Digital Content is available in the text.